Analysis of the effect of Energy Prices on Stock Indexes During the Epidemic Crisis - Guliyeva, Shafa (International Journal of Energy Economics and Policy, 2023)
Petroleum and natural gas, which are among the most used energy sources in the world, have a significant impact on financial markets and macroeconomic indicators as they are used as raw materials in many fields. For this reason, US, England, Japan, Russia, Turkey, Brazil, and India, as energy importers and developing countries, may be affected positively or negatively by changes in energy prices. The main purpose of this study is to examine the correlation between Brent oil, crude oil (WTI), and natural gas (NG) prices and Moscow Stock Exchange Index (RTSI), Borsa Istanbul Index (XU100), Bovespa Brazilian Stock Exchange Index (BVSP), Indian National Stock Exchange Nifty 50 Index (NSEI), Standard and Poor’s 500 Index (S and P 500), London Stock Exchange (FTSE 100), and Тokyo Stock Exchange (N225). In the study, weekly data between February 16, 2020 and December 26, 2021 were examined. Vector autoregressive (VAR) model was used to examine the correlation between the variables included in the analysis, and the direction of the correlation between the variables was determined by the Granger causality test. According to the results of the VAR model, Brent oil and crude oil prices have significant effects on the indices included in the analysis; however, natural gas price does not have a significant effect on indices, Brent oil, and crude oil prices. On the other hand, the results of the Granger causality test confirm the findings of the VAR analysis. Granger causality test results reveal that in Granger’s sense, only BVSP and NSEI are the cause of Brent oil price, RTSI, BVSP, NSEI, XU100, S and P 500, FTSE 100, and N225 are the cause of WTI, and WTI is the cause of NSEI.